2011
DOI: 10.1111/j.1939-3938.2011.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

The emotional challenges faced by Sexual Assault Nurse Examiners: “ER nursing is stressful on a good day without rape victims”

Abstract: Although research has indicated that counselors, advocates and social workers who assist rape victims experience vicarious trauma or psychological consequences as a result of their exposure to victims' traumatic experiences, little is known about Sexual Assault Nurse Examiners' (SANEs') experiences. This qualitative research explores SANEs' experiences of vicarious trauma and burnout as a result of treating rape victims, and the coping strategies they implement to reduce both. Data from interviews with 39 SANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 37 publications
(100 reference statements)
1
39
0
Order By: Relevance
“…These SANE nurses described the same concern regarding triggering emotional distress or re-traumatizing SA survivors when addressing the SA as expressed by our participants (Maier, 2012). Additionally, they described their own experiences of emotional challenges when dealing with SA such as vicarious trauma and burnout (Maier, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…These SANE nurses described the same concern regarding triggering emotional distress or re-traumatizing SA survivors when addressing the SA as expressed by our participants (Maier, 2012). Additionally, they described their own experiences of emotional challenges when dealing with SA such as vicarious trauma and burnout (Maier, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In those who provide sexual abuse treatment, male gender, age and childhood neglect were predictors of disruptive cognitions [5]. In one study, 67 % of sexual assault nurse examiners reported vicarious trauma, emotional demands associated with the job and burnout [6]. Another study looking at social workers who work closely with sexually abused clients described the social workers as experiencing denial, anger, depression, and disruption in their lives [7].…”
Section: Introductionmentioning
confidence: 97%
“…Emotional distress has been described in social workers and nurses who counsel victims of trauma [12, 13]. Emotional distress is well documented in women who suffer domestic abuse [14, 15] and manifests as psychological symptoms of distress (feeling worried or tense, headaches, poor digestion, tiredness), including depression and anxiety [16].…”
Section: Introductionmentioning
confidence: 99%